2022
DOI: 10.1002/adom.202102615
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Arrays of 3D AuNP‐Capped VO2 Shells and Their Temperature‐Tunable SERS Performance

Abstract: In this work, periodic arrays of 3D composite structures consisting of gold nanoparticle (AuNP) capped VO2 shells on self‐assembled highly‐ordered SiO2 microspheres have been designed and fabricated, and their temperature‐tunable surface‐enhanced Raman scattering (SERS) performance is investigated. The results show that the SERS intensity enhancement factor (EF) for R6G molecules adsorbed on the AuNP‐capped VO2 shells increases from 8.3 × 105 to 3.9 × 106 when triggering the semiconductor‐to‐metal phase transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 44 publications
0
12
0
1
Order By: Relevance
“…Nano/microstructured engineering surfaces, with either rigid or irregular structures, can wavelength-sensitively interact with incident photons to regulate their electromagnetic field distribution at the surface or interfaces, resulting in drastic differences from conventional planar coating surfaces. For VO 2 -based energy-efficient windows, various specially designed structures at the nano- and microscales have been developed, to suppress the surface reflection, , enhance the luminous transmittance and solar energy modulation ability, ,, optimize color, , and regulate the localized surface plasma. , …”
Section: Vanadium Dioxidementioning
confidence: 99%
“…Nano/microstructured engineering surfaces, with either rigid or irregular structures, can wavelength-sensitively interact with incident photons to regulate their electromagnetic field distribution at the surface or interfaces, resulting in drastic differences from conventional planar coating surfaces. For VO 2 -based energy-efficient windows, various specially designed structures at the nano- and microscales have been developed, to suppress the surface reflection, , enhance the luminous transmittance and solar energy modulation ability, ,, optimize color, , and regulate the localized surface plasma. , …”
Section: Vanadium Dioxidementioning
confidence: 99%
“…6−11 In 2008, Landy et al designed a metasurface device capable of perfect absorption, which consists of a surface metal resonator, a polyimide dielectric layer, and a bottom metal strip. 12,13 The results showed that the absorptance was above 99% at 11.48 GHz. The absorber had high absorptance and a small unit size, but its absorption frequency band was narrow, and it was very sensitive to the polarization direction of electromagnetic waves.…”
Section: Introductionmentioning
confidence: 98%
“…Metasurfaces can achieve unique properties, such as negative permittivity, negative permeability, a negative refractive index, an inverse Doppler effect, and inverse Snell’s law through artificial design. These unique electromagnetic properties of the metasurface have attracted widespread attention. The metasurface absorber can achieve high absorption of THz waves and currently shows great applicational potential in medicine, biology, and aerospace exploration. In 2008, Landy et al designed a metasurface device capable of perfect absorption, which consists of a surface metal resonator, a polyimide dielectric layer, and a bottom metal strip. , The results showed that the absorptance was above 99% at 11.48 GHz. The absorber had high absorptance and a small unit size, but its absorption frequency band was narrow, and it was very sensitive to the polarization direction of electromagnetic waves.…”
Section: Introductionmentioning
confidence: 99%
“…In recent research, nanocomposites were used in electrochemical applications, including as sensors, owing to their high surface area, high conductivity, and good electrocatalytic properties [ 3 , 16 , 17 , 18 , 19 , 20 , 21 ]. More recently, magnetic Fe 3 O 4 nanoparticles have shown excellent magnetic properties, electrical conductivity, chemical stability, biocompatibility, and low toxicity.…”
Section: Introductionmentioning
confidence: 99%